Efeito da distribuição microestrutural de fases mineralógicas na susceptibilidade de rochas da região nordeste para o desenvolvimento da reação álcali-agregado - Andrade, Tibério Wanderley Correia de Oliveira (2019)
Since 2005, when the RAA was diagnosed in building foundations in the city of Recife, state of Pernambuco, national engineering and academia have taken a very proactive stance towards the problem. Until then, in Brazil, the concern and prevention for this mechanism of concrete deterioration was summed up to major infrastructure works, mainly dams and hydroelectric. Until then, Brazilian normalization did not contemplate norms that dealt with the issue, which could guide national engineering to prevent the problem. Soon after these cases and disclosure at national level, an ABNT commission was formed to develop specific standards on AAR. In 2008, these sets of standards (NBR 15.577) entered into force and is already in its second review. With awareness of the problem, construction companies and contractors throughout the country began to worry about the reactivity of households, requiring their concrete suppliers and quarries, reactivity and mitigation tests. With regard to academia, many research groups across the country have begun to produce scientific work whose focus is the alkali-aggregate reaction. In the vast majority of these studies, technological trials defined by Brazilian normalization are used. The research proposed in this work will have an unprecedented approach, using DRX and SEM techniques to identify microstructural characteristics that can lead to proof the potential for reactivity of aggregates by these unconventional techniques for RAA. For this research, 15 large aggregates from several regions of the Northeast are being used, with different levels of reactivity. In these aggregates will be carried out all the technological tests recommended as a standard for validation of the results obtained. .